DEVELOPMENT AND PATHOGENICITY OF INFECTIVE JUVENILES ORIGINATING VIA ENDOTOKIA MATRICIDA IN AXENIC STEINERNEMATID NEMATODES - Yuliantoro Baliadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Development and insecticidal activity of axenic infective juveniles (IJs) originating from endotokia matricida in maternal bodies of Steinernema glaseri and S. carpocapsae were investigated with a comparison to IJs developed in monoxenic culture. In comparison with the monoxenic steinernematids, the axenic ones grew slower and produced fewer IJs when they were cultured in a sterile chicken liver extract medium supplement with an autoclaved nematode infected Galleria mellonella larva. The phenomena of endotokia matricida, an intra-uterine development of hatched juvenile, occurred in an axenic culture as did the monoxenic ones. Although it occurred faster in monoxenic culture, the ratio of females bearing endotokia matricida was more numerous in axenic ones. These axenic females also produced IJs through the endotokia matricida phenomenon. Compared to the normal IJs develop in monoxenic culture, the IJs originated via endotokia matricida of axenic nematodes showed lower insecticidal activity and it could not reproduce in G. mellonella cadaver.